PSYCHOLOGICAL INTERVENTIONS AS A TOOL FOR INCREASING THE EFFECTIVENESS OF DISEASE TREATMENT - Shoyimova Shokhista Sanakulovna (Web of Journals Publishing, 2025)
This article examines the impact of psychological interventions on treatment outcomes for diseases of various etiologies. It examines the use of cognitive behavioral therapy, meditation, hypnosis, and other methods to improve clinical outcomes and enhance patients' quality of life. It also examines the mechanisms by which psychological factors influence physical health and prospects for further research in this area.
Keywords: Psychological interventions, cognitive behavioral therapy, meditation, hypnosis, disease treatment, effectiveness, quality of life, psychosomatics, clinical outcomes.